Tempeh Inoculum Application Test of Rhizopus oryzae with Rice and Cassava Flour as Substrate at Sanan Tempeh Industries â Kodya Malang - Sukardi, Sukardi; Wignyanto, Wignyanto; Purwaningsih, Isti (Jurnal Teknologi Pertanian, 2008)
This research was designed to obtain high quality dried tempeh inoculum (powder) and to know the best level of inoculum for small medium industrial scale. Also it was designed to know the preference of consumers. Experimental design employed in this research was completely randomized design comprosed of one factor i.e. the level of R. oryzae concentration consisted of 0.9% w/w; 0.7% w/w; 0.5% w/w; 0.3% w/w; and 0.1% w/w. The initial R. oryzae spore of the starter was 1,3x107 cfu/g. The best treatment was determided by multiple atribute method. The application test of the best inoculum was done at 3 tempeh small industries and the produced tempeh was analyzed by sensory test.The best level of R. oryzae pure culture addition was 0.5% based on substrate weight, and the total microbial of dried inoculum was 8.02 x 107 cfu/g (7.90 log cfu/g) with the percentage of viable mold after I month was 89,52%. The total number of mold after mixing with rice flour was 3.04 x 107 cfu/g (6.893 log cfu/g), the percentage of viable mold was 90.92%, and the percentage of contaminating bacterium was 41.75%. The end piece of cassava could be used as substrate for tempeh inoculum production from pure culture of R. oryzae and it had yield of 41.70% and moisture content of 6.57%. The best addition of R. oryzae inoculum in producing tempeh was 0.15%, and the consumers preference of texture was 8,07 (like very much), the appearance was 7,67 (like), color was 7.47 (like), the aroma was 7.47 (like), and taste was 8 (like very much).Keywords: tempeh inoculum, pure culture, dried inoculum, tempeh industries